2011
DOI: 10.1108/09513551111121329
|View full text |Cite
|
Sign up to set email alerts
|

Changed governance of public sector organisations=challenged conditions for intra‐professional relations?

Abstract: Purpose -Effects of NPM in professional work are often discussed on an overriding level, and professionals' own experiences of their working conditions in their specific work contexts have been less discussed (Hasselbladh et al. and Liljegren). In an attempt to consider this concern, this paper seeks to focus on individual professionals, exemplified by teachers and nurses, and their experiences of intra-professional relations, i.e. teachers' relations with other teachers and nurses' relations with other nurses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 18 publications
(13 reference statements)
2
20
0
Order By: Relevance
“…For instance, in terms of how the workplace opens up for, or constrains, informal competence development, which is whether or not teachers can easily share with subject colleagues. These findings were neither new nor surprising; rather they were consistent with our previous studies (Jansson & Parding, 2011;Parding & Abrahamsson, 2010). Moreover, it could be argued that the local differences mirrored regional differentiation.…”
Section: Differentiated Conditionssupporting
confidence: 89%
See 2 more Smart Citations
“…For instance, in terms of how the workplace opens up for, or constrains, informal competence development, which is whether or not teachers can easily share with subject colleagues. These findings were neither new nor surprising; rather they were consistent with our previous studies (Jansson & Parding, 2011;Parding & Abrahamsson, 2010). Moreover, it could be argued that the local differences mirrored regional differentiation.…”
Section: Differentiated Conditionssupporting
confidence: 89%
“…Moreover, it could be argued that the local differences mirrored regional differentiation. In other words, in relation to our previous research (Jansson & Parding, 2011;Parding & Abrahamsson, 2010), as well as to the empirical data presented in this paper, it can be argued that the issue of context must be seen in a broader sense. The local and regional circumstances of a workplace must be considered when examining the conditions for competence development among welfare-sector professionals, as school choice and municipalization reforms seem to have complex consequences on various levels.…”
Section: Differentiated Conditionssupporting
confidence: 56%
See 1 more Smart Citation
“…The main finding of this paper was that the conditions for competence development, in the context of school choice reform and municipalization, could be described as differentiated. It became clear that the intended-and perhaps unintended-consequences of state reform(s) were complex (see also Jansson & Parding, 2011). The analysis of the interviews revealed that the geographic location, budgetary resources, and size and age of a workplace were central to understanding how different interviewees described and experienced their working conditions.…”
Section: Differentiated Conditionsmentioning
confidence: 99%
“…For example, a previous study on teachers and nurses found that changes in an organization resulted in changes in intra-professional relations that conflicted with the collective building of a knowledge base (i.e., collegiality decreased) (Jansson & Parding, 2011). Cheetham and Chivers (2001) highlighted the importance of professionals being physically close to colleagues, as this facilitates the development of competence in everyday work.…”
Section: Conclusion and Avenues For Further Researchmentioning
confidence: 99%